THESE ARE INDIGENOUS LANDS: Foregrounding Settler Colonialism and Indigenous Sovereignty as Primary Contexts for Canadian Environmental Social Work - Hiller, Chris; Carlson, Elizabeth (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2018)
The recent upsurge of interest regarding environmental social work is unfolding against a backdrop of centuries of continuous struggle on the part of Indigenous peoples to protect their lands and waters. In this article, we consider the ways in which environmental social work frameworks engage the realities and resistances of Indigenous peoples in the context of settler colonialism. We contend that to ethically engage with environmentalism, social workers living and working on Indigenous territories must understand and resist settler colonialism, our implication in upholding its structure and practices, and its contribution to ecological destruction. Drawing upon the work of Indigenous scholars, we briefly describe Indigenous peoples’ conception of their relationships to land and sovereignty and how settler colonialism as a structure is organized with the explicit aim of eliminating these relationships. We then review prominent texts addressing several competing environmental social work frameworks, considering how each takes up (or not) histories of colonialism and Indigenous dispossession and addresses Indigenous identities, relations to land, and assertions of sovereignty. We conclude by offering principles and practices that might foreground the disruption of settler colonialism and respect for Indigenous sovereignty as necessary frameworks for Canadian environmental social work.